Occurrence of biflagellate spermatozoa in Cetopsidae, Aspredinidae, and Nematogenyidae (Teleostei : Ostariophysi : Siluriformes) - Spadella, Maria Angelica; Oliveira, Claudio [UNESP]; Quagio-Grassiotto, Irani (Springer, 2006)
In the present study spermiogenesis was investigated in Cetopsis coecutiens (Cetopsidae), and Bunocephalus amazonicus (Aspredinidae), while spermatozoa ultrastructure was investigated in C. coecutiens, B. amazonicus, and Nematogenys inermis (Nematogenyidae). Aspredinidae and Cetopsidae share a spermatogenesis of the semicystic type, and a particular type of spermiogenesis process not reported in any fish group. In the three species analyzed, spermatozoa are biflagellate with flagella having the classical axoneme formulae (9 + 2). The analysis of thirteen characters showed the presence of eight characters shared by Cetopsidae and Aspredinidae, and six characters shared by Cetopsidae and Nematogenyidae, which may suggest that these three families may be more related than actually hypothesized, comprising a very primitive siluriform lineage originated after Diplomystidae.
Keywords: fish evolution; catfish; sperm; semicystic spermatogenesis; morphology